PENYUTRADARAAN PROGRAM MAGAZINE“MUSICOLOGY” EPISODE MUSIK JAZZDENGAN GAYA VISUAL POP - FAJRI, Zulianita (FSMR - ISI Yogyakarta, 2015)
Television is the most effective media for one way communication in order to convey a message. Television is not a mere means of communication. It also serves as a media for entertainment, education and information. Thus, many television stations offer interesting programs to attract viewers. The problem is that not all of those programs possess educational value.The creation of the jazz music episode for this magazine program entitled “Musicology” aims to give an alternative program containing the values of education, information, as well as entertainment to the viewers. This program offers, not only an interesting narrative concept, but also a captivating visual concept.The program is presented using the visual pop a style, a style perfectly matched for the targeted audiences, youths and young generations. The visual pop style can be observed in, among others, the graphic pattern which uses bright colors, striking typography, and fast-tempo-music to project energetic, joyous, and dynamic impressions without undermining the messages and information intended to be given.